THE IMPLEMENTATION OF SALES PROMOTION AND EASE OF PAYMENT METHODS FOOD AND BEVERAGE BUSINESSES IN PARAPAT TOURIST AREA ON CUSTOMER REVISIT INTEREST - Syahrul Syahrul; Riana Handayani Silalahi; Sepdwiyana Donargo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the impacts of sales promotion, payment methods, and the simultaneous effect of both sales promotion and payment methods on customer revisit intention in the food and beverage business in Parapat. The data analysis used in this research is quantitative analysis, processed using the Statistical Package for the Social Sciences (SPSS). This type of research is associative or causal, aiming to determine the relationship or influence of sales promotion and the ease of payment methods on customer revisit intention. The results show that the t-value of 5.783, which is greater than the t-table value of 1.984, with a correlation value of 0.869. This indicates that sales promotion has a positive and significant influence, categorized as "very strong," on customer interest in revisiting food and beverage establishments in Parapat. Furthermore, a positive influence and a strong category were found for the ease of payment methods variable on revisit intention, with a value of 0.742. This signifies that the ease of payment methods has a positive, significant, and strong relationship with customer revisit intention. The simultaneous analysis yielded a value of 5.168, exceeding the t-table of 1.798, with a correlation coefficient of 0.917, placing the influence of both variables in the "very strong" category. Therefore, sales promotion and the ease of payment methods collectively have a positive and significant influence on customer revisit intention in Parapat. Based on the linear regression equation, visitor intention to return will increase by 0.253 for every 1% increase in sales promotion, and similarly, revisit intention will increase by 0.232 for every 1% increase in the ease of payment methods.